2018
DOI: 10.3390/insects10010002
|View full text |Cite
|
Sign up to set email alerts
|

Annual Abundance and Population Structure of Two Dung Beetle Species in a Human-Modified Landscape

Abstract: Population studies are essential for understanding different aspects of species’ biology, estimating extinction probability, and determining evolutionary and life history. Using the mark-recapture method, we studied the abundance and population structure of dung beetle species (Deltochilum mexicanum and Dichotomius satanas) over one year in a human-modified landscape in Mexico. We captured 1960 individuals with a net recapture rate of 11%. Deltochilum mexicanum had a higher rate of recapture (14%) than Dichoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 63 publications
4
38
0
1
Order By: Relevance
“…Finlay-Doney and Walter [9] reported that temperature can stimulate or suppress insect pest genetic potential, mortality and fecundity, and host plants. Danks [10] studied the elements of seasonal adaptation in insects and found the air temperature, air relative humidity, aridity, food availability, sensitivity of environmental signals, interaction among insect species and other factors as responsible elements controlling insect abundance [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Finlay-Doney and Walter [9] reported that temperature can stimulate or suppress insect pest genetic potential, mortality and fecundity, and host plants. Danks [10] studied the elements of seasonal adaptation in insects and found the air temperature, air relative humidity, aridity, food availability, sensitivity of environmental signals, interaction among insect species and other factors as responsible elements controlling insect abundance [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The differences observed in the number of individuals in each stage of sexual maturity suggest that the population dynamic of D. satanas is characterised by high migration (exit of individuals), as has been observed at landscape scale (Barretto et al 2018). Given that approximately 15% of the total number of individuals dissected were mature, we believe that immature and maturing individuals have a greater probability of dispersion at different times throughout the year.…”
Section: Stages Of Sexual Maturitymentioning
confidence: 55%
“…The results of this study suggest that D. satanas is a protogynous species, as was found for Onthophagus incensus under field conditions (Martínez et al 1998). According to Degen et al (2015), protogyny is characteristic in populations in which males present greater mortality, coinciding with that observed for populations of D. satanas, due to intrasexual competition and greater male mobility (Barretto et al 2018). However, although the phenological cycle of insects is usually characterised by differential emergence between sexes, protogyny is rarely observed (Van Timmerman et al 2000).…”
Section: Reproductive Phenologymentioning
confidence: 80%
See 2 more Smart Citations